Improving Mathematics Learning Outcomes in Systems of Linear Equations in Two Variables Using the Problem-Based Learning Model - Rahmat Rahmat; Ismail Djakaria; Novianita Achmad (Scimadly Publishing, 2026)
This study aims to improve students' mathematics learning outcomes on Systems of Linear Equations in Two Variables (SLETV) through the implementation of the Problem-Based Learning (PBL) model. This type of research is Classroom Action Research (CAR) conducted at SMP Negeri 1 Suwawa during the even semester of the 2024/2025 academic year, with 31 eighth-grade students (class VIII-B) as subjects. The research took place in a single cycle consisting of four meetings (three learning process meetings and one final test meeting). The instruments used included Lesson Plans, Student Worksheets, observation sheets for teacher and student activities, and learning achievement tests. Observation results indicated that the percentage of teacher activity in the